Inovasi Pengembangan Ekonomi Desa melalui Digitalisasi Berbasis Potensi Lokal Masyarakat Desa Lompotoo - Melan Angriani Asnawi; Citra Aditya Kusuma; Isra Putri Arieka M. Yasin Kiu (Universitas Negeri Gorontalo, 2025)
This community service program was implemented in Lompotoo Village to address low digital literacy, limited MSME branding, and the suboptimal utilization of local resources. The activities included digital marketing training, content creation workshops, and branding education based on the village’s local potential. A participatory approach was used through four stages: preparation, implementation, evaluation, and follow-up. The results show a significant increase in community digital understanding, demonstrated by a 38–39 point improvement in pre-test and post-test scores. Additionally, a local product innovation called “LOPBOBA” was successfully developed, and the village website began operating as a promotional platform for MSMEs. This program has strengthened community digital skills, enhanced village identity, and supported sustainable local economic growth.